2019
DOI: 10.4103/jfmpc.jfmpc_450_18
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of geriatric anemia: A hospital-based observational study in North India

Abstract: Background: Geriatric anemia is a global health problem because of its high prevalence and associated significant morbidity and mortality. Aim: The objectives of this study were to estimate the pattern of anemia in the elderly patients and the underlying etiology of anemia. Research Design and Methods: This was a hospital-based prospective observational study, conducted in patients aged 60 years and above at PGIMER, Chandigarh, a tertiary car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
2
3
0
1
Order By: Relevance
“…In our study, hemoglobin levels decreased significantly with increasing age (Table 2) and normocytic anemia (66.4%) was the most common form, similar to previous studies (11,23). The prevalence of anemia increases after the age of 60 to 65 years and becomes more pronounced over the age of 80 (22).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, hemoglobin levels decreased significantly with increasing age (Table 2) and normocytic anemia (66.4%) was the most common form, similar to previous studies (11,23). The prevalence of anemia increases after the age of 60 to 65 years and becomes more pronounced over the age of 80 (22).…”
Section: Discussionsupporting
confidence: 90%
“…Iron deficiency is relatively common and frequently diagnosed in older individuals. In a hospital-based prospective observational study among 105 older patients, iron deficiency was found in 26 (24.8%) patients [ 40 ]. In addition, results of a cross-sectional, retrospective analysis of inpatients and outpatients aged ≥64 years demonstrated that 21.1% of the patients were anemic in which 14.4% and 28.2% had absolute and functional iron deficiency, respectively [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…11,18,19 The prevalence of anemia of 47.3% was observed in the under 24 years age group which is comparable with the study by Sharma et al (38%) whereas in a study by Suryanarayana et al in Kashmir the prevalence of anemia of 93.67% (Table 3). 12,19 Early age at marriage and poor iron stores contributes to high prevalence in this age group. A prevalence of 58% was observed in booked patients which could be due to noncompliance with iron therapy and lack of frequent hemoglobin estimation.…”
Section: Discussionmentioning
confidence: 99%